Low vision rehabilitation : a practical guide for occupational therapists - Scheiman, Mitchell; Scheiman, Maxine; Whittaker, Steven; Freeman, Paul B.; Sokol-McKay, Debra A. (Slack Inc., 2007)
Presents an emerging model in which occupational therapists practice as part of a team of vision rehabilitation professionals serving adults with low vision. Occupational therapists offer a unique contribution to the vision rehabilitation team, with a focus on meaningful occupational goals, the incorporation of occupation into therapy, and the orchestration of environmental, social, and non-visual personal factors into a treatment plan. The authors have developed a practical and straightforward text outlining an evaluation approach to interventions that focus on recovering occupational performance in adults.